1999
DOI: 10.1002/(sici)1521-3927(19990301)20:3<116::aid-marc116>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Stopped-flow polymerizations of ethene and propene in the presence of the catalyst systemrac-Me2Si(2-methyl-4-phenyl-1-indenyl)2ZrCl2/methylaluminoxane

Abstract: SUMMARY: The kinetics of ethene and propene polymerization at 20 -60 8C in the presence of the homogeneous catalyst system rac-Me 2 Si(2-methyl-4-phenyl-1-indenyl) 2 ZrCl 2 /methylaluminoxane was investigated by means of stopped-flow techniques. The specific rate of chain propagation, measured at the very short reaction times typical of this method, turned out to be L10 2 times higher for ethene than for propene; this suggests that diffusion limitations through the poly(ethylene) precipitating at longer reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 12 publications
3
97
0
1
Order By: Relevance
“…An interesting feature of the whole catalyst family is an unusually low [for Ziegler-Natta catalysis (26)(27)(28)] turnover frequency, as if the polymerization occurred ''at slow motion.'' In particular, for the most sterically congested catalysts 4, 6, and 7 we measured average chain growth times of several hours at 25°C (under the conditions described in Materials and Methods).…”
Section: The Coordination Around Zr Is Distorted-octahedral With Tranmentioning
confidence: 99%
“…An interesting feature of the whole catalyst family is an unusually low [for Ziegler-Natta catalysis (26)(27)(28)] turnover frequency, as if the polymerization occurred ''at slow motion.'' In particular, for the most sterically congested catalysts 4, 6, and 7 we measured average chain growth times of several hours at 25°C (under the conditions described in Materials and Methods).…”
Section: The Coordination Around Zr Is Distorted-octahedral With Tranmentioning
confidence: 99%
“…O método Stopped-Flow ¶ (SFM) [92] , comumente usado em estudos de cinética homogênea e para análises de polimerizações em solução e em suspensão [93][94][95] , também é extensamente empregado para estudo do desenvolvimento morfológico de partículas poliméricas em polimerizações conduzidas com catalisadores heterogêneos em experimentos realizados com tempos de polimerização extremamente curtos em condições industriais de operação [96][97][98][99][100][101][102][103][104] . Seguindo o conceito similar ao SFM, Machado et al [105] desenvolveram um novo aparato experimental (denominado de Short Stop Reactor ** -SSR) especialmente para o estudo da polimerização nascente e a fragmentação de catalisadores heterogêneos em polimerizações de olefinas conduzidas em fase gasosa.…”
Section: A Etapa De Prepolimerizaçãounclassified
“…For metallocene/MAO-catalyzed ethylene and propylene polymerization, the average lifetime of a growing chain is typically less than seconds, and time-related effects can only be observed with stopped-flow techniques. [11] The fit of the first-order copolymerization equation serves only for illustration. Detailed 13 C NMR analysis of the microstructure has revealed that the penultimate model (second-order Markovian statistics) describes the E-N copolymerization better.…”
Section: Determination Of Kinetics Parameters and Number Of Active Sitesmentioning
confidence: 99%
“…Busico et al [11] have used Equation (3) to quantify the kinetics of the stopped flow polymerizations of ethylene and propylene.…”
Section: Determination Of Kinetics Parameters and Number Of Active Sitesmentioning
confidence: 99%
See 1 more Smart Citation